A cell membrane-anchored nanoassembly with self-reporting property for enhanced second near-infrared photothermal therapy. (December 2021) - Long, Zi; Hu, Jing-Jing; Yuan, Lizhen; Duan, Chong; Dai, Jun; Zhen, Shijie; Zhao, Zujin; Lou, Xiaoding; Xia, Fan
Highlights: High therapeutic efficiency is due to the deeper penetration depth of laser and prolonged cell membrane anchoring ability. Tumor cell membrane anchoring could monitor therapeutic feedback to avoid excessive phototoxicity. We first report the cell membrane image-guided NIR-II PTT to self-report the therapeutic effect. therapeutic effect. Graphical Abstract: ga1 Abstract: Tumor residues caused by limited light penetration depth and inadequate concentration of photothermal agents (PTAs) in photothermal therapy (PTT) easily result in the tumor recurrence and metastasis. In turn, treatment overdose would increase unavoidable damage to the nearby normal tissues. To solve this dilemma, we design a cell-membrane-anchored nanoassembly (designated as DTPRR9 ) for aggregation-induced emission fluorogens (AIEgens) imaging guided second near-infrared (NIR-II) PTT, which can not only achieve a higher therapeutic effect through locating and retaining on the tumor cell membrane, but also monitor the therapeutic feedback to avoid excessive phototoxicity. DTPRR9 nanoassemblies are obtained by co-encapsulating AIEgens and NIR-II absorbing semiconducting polymers via amphiphilic polymers, and then further modified with RR9 peptide (RGDRRRRRRRRRC). Under a 1064 nm laser irradiation, DTPRR9 with high photothermal conversion efficacy (η = 70.4%) could directly disrupt cell membrane by in situ generated hyperthermia. Moreover, the translocation of AIE fluorescence from the damaged cell membrane could be used to self-report the therapeutic effect. This cell-membrane-anchored nanoassembly brings an advanced strategy to surmount difficulties of low therapeutic efficiency and severe potential side effects in PTT.